Examining the role of flame topologies and in-cylinder flow fields on cyclic variability in spark-ignited engines using large-eddy simulation. (October 2018) - Zhao, Le; Moiz, Ahmed Abdul; Som, Sibendu; Fogla, Navin; Bybee, Michael; Wahiduzzaman, Syed; Mirzaeian, Mohsen; Millo, Federico; Kodavasal, Janardhan
In this work, we have studied cycle-to-cycle variation in a spark-ignited engine using large-eddy simulation in conjunction with the G -equation combustion model. A single cylinder of a four-cylinder port-fueled spark-ignited engine was simulated. A total of 49 consecutive full cycles were computed. The operating condition studied in this work is stoichiometric and stable and represents a load of 16 bar brake mean effective pressure and an engine speed of 2500 r/min. The computational fluid dynamics simulation shows good agreement in terms of in-cylinder pressure prediction with respect to the experiments and is also able to capture the range of cycle-to-cycle variation observed in experiments. Furthermore, neither the simulation nor the experiments show any distinguishable pattern in the sequence of high and low cycles. We numerically decoupled the effects of variations in equivalence ratio fields and velocity fields to isolate the effects of differences in the velocity field and differences in the equivalence ratio field on flame development and propagation. Based on this study, we inferred that for this engine, under the operating conditions studied, the differences in burn rates can be attributed to the differences in the velocity flow-field in the region around the spark gap during ignition. We then performed an analysis to identify the correlation between peak cylinder pressure and flame topologies over all the simulated cycles. We found that high cycles (higher peak cylinder pressure values) are strongly correlated to flatter flame volume shapes (flattened in the piston-to-head direction) and volumes that are more symmetric about the ignition axis. In addition, these kinds of flame volumes were found to correlate well with lower values of prior-to-ignition velocity going from the intake to the exhaust side (mean flow caused by tumble) at the spark and also higher values of prior-to-ignition velocity in the piston-to-head direction.